RETRACTED: Adenine Combined with Cisplatin Promotes Anticancer Activity against Hepatocellular Cancer Cells through AMPK-Mediated p53/p21 and p38 MAPK Cascades - Jhen-Yu Huang; You-Cian Lin; Han-Min Chen; Jiun-Tsai Lin; Shao-Hsuan Kao (Pharmaceuticals, 2022)
Cisplatin has been widely used in cancer treatments. Recent evidence indicates that adenine has potential anticancer activities against various types of cancers. However, the effects of the combination of adenine and cisplatin on hepatocellular carcinoma (HCC) cells remain sketchy. Here, our objective was to elucidate the anticancer activity of adenine in combination with cisplatin in HCC cells and its mechanistic pathways. Cell viability and cell cycle progression were assessed by the SRB assay and flow cytometry, respectively. Apoptosis was demonstrated by PI/annexin V staining and flow cytometric analysis. Protein expression, signaling cascade, and mRNA expression were analyzed by Western blotting and quantitative RT-PCR, respectively. Our results showed that adenine jointly potentiated the inhibitory effects of cisplatin on the cell viability of SK-Hep1 and Huh7 cells. Further investigation showed that adenine combined with cisplatin induced higher S phase arrest and apoptosis in HCC cells. Mechanically, adenine induced AMPK activation, reduced mTOR phosphorylation, and increased p53 and p21 levels. The combination of adenine and cisplatin synergistically reduced Bcl-2 and increased PUMA, cleaved caspase-3, and PARP in HCC cells. Adenine also upregulated the mRNA expression of p53, p21, PUMA, and PARP, while knockdown of AMPK reduced the increased expression of these genes. Furthermore, adenine also induced the activation of p38 MAPK through AMPK signaling, and the inhibition of p38 MAPK reduced the apoptosis of HCC cells with exposure to adenine combined with cisplatin. Collectively, these findings reveal that the combination of adenine and cisplatin synergistically enhances apoptosis of HCC cells, which may be attributed to the AMPK-mediated p53/p21 and p38 MAPK cascades. It suggests that adenine may be a potential adjuvant for the treatment of HCC in combination with cisplatin.